Globalization and the Development of Contemporary Natural Sciences - Sikora, Marek (Sensus Historiae, 2022)
The article discusses the influence of globalization on the development of contemporary natural sciences. These sciences are presented from two different points of view: theoreticism and laboratory sciences. In the latter case, the author emphasizes close relations between science and technology. He defends the thesis that, especially in the period of globalization, both fields increasingly overlap, creating technoscience. Technoscience, unlike theoreticism, subordinates its research activity not only to epistemic, but also to non-epistemic values, among which ethical and social values play a key role. Turning towards these values, technoscience faces the problem of ethical and social responsibility for the intended and unintended consequences of its products. This problem is particularly relevant in the context of what Shoshana Zuboff calls the era of surveillance capitalism.